Primary leiomyosarcoma of the bone: a case report and a review of the literature. Issue 45 (November 2017) - Recine, Federica; Bongiovanni, Alberto; Casadei, Roberto; Pieri, Federica; Riva, Nada; De Vita, Alessandro; Mercatali, Laura; Liverani, Chiara; Spadazzi, Chiara; Miserocchi, Giacomo; Fausti, Valentina; Amadori, Dino; et al.
Abstract: Rationale: Leiomyosarcoma (LMS) is a malignant sarcoma that can occur in different anatomic sites, including the bone, showing similar histological characteristics but heterogeneous clinical behavior and prognosis. Primary bone LMS was first described in 1965. It is a very rare sarcoma, accounting for <0.7% of all primary malignant bone tumors. Patient concerns: We report the case of a 52-year-old male with primary bone LMS who presented with a solitary osteolytic lesion with focal cortical destruction in the left clavicle, seen on an x-ray and subsequent computed tomography (CT) scan. Diagnosis: The multidisciplinary Osteoncology team of our institute planned a biopsy that revealed the presence of spindle and pleomorphic cells with a positive reaction for smooth muscle actin and desmin at immunohistochemical analysis, without the presence of cartilage or bone matrix. These results were consistent with a high-grade malignant LMS arising from the bone. Interventions: Complete surgical resection of the tumor was performed and a decision was made with the patient not to proceed with adjuvant chemotherapy or radiotherapy. Outcomes: After more than 1 year of surgery, the patient is well, with no evidence of recurrent or metastatic disease. Follow-up is ongoing. Lessons: Little is known about the biology and clinical behavior of bone LMS due to its extreme rarity. A multidisciplinary team in a specialized center is needed for the optimal management of the disease. Surgery with a curative intent is the cornerstone of treatment of localized disease. No data are available about chemotherapy in neoadjuvant, adjuvant, or advanced settings. Further research is needed to identify more effective therapies.